2019
DOI: 10.1126/sciadv.aav2189
|View full text |Cite
|
Sign up to set email alerts
|

No high Tibetan Plateau until the Neogene

Abstract: The Late Paleogene surface height and paleoenvironment for the core area of the Qinghai-Tibetan Plateau (QTP) remain critically unresolved. Here, we report the discovery of the youngest well-preserved fossil palm leaves from Tibet. They were recovered from the Late Paleogene (Chattian), ca. 25.5 ± 0.5 million years, paleolake sediments within the Lunpola Basin (32.033°N, 89.767°E), central QTP at a present elevation of 4655 m. The anatomy of palms renders them intrinsically susceptible to freezing, imposing up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
220
1
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 221 publications
(251 citation statements)
references
References 43 publications
12
220
1
8
Order By: Relevance
“…The relatively recent divergence time between the alpine N. parkeri and the subalpine N . pleskei / N. ventripunctata from the eastern Plateau margin (< 5 Mya) fits the concept of a final uplift of the Tibetan Plateau rather late in the Neogene (Su et al, ). An almost identical biogeographic history has been demonstrated in Scutiger boulongeri , the Tibetan alpine toad (Hofmann et al, ).…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…The relatively recent divergence time between the alpine N. parkeri and the subalpine N . pleskei / N. ventripunctata from the eastern Plateau margin (< 5 Mya) fits the concept of a final uplift of the Tibetan Plateau rather late in the Neogene (Su et al, ). An almost identical biogeographic history has been demonstrated in Scutiger boulongeri , the Tibetan alpine toad (Hofmann et al, ).…”
Section: Discussionsupporting
confidence: 74%
“…Indeed, genetic separation, diversity, and geographical distribution of Himalayan spiny frogs seem to be best explained by a South Tibetan origin rather than by the alternative immigration or strict vicariance scenario. A Tibetan origin of high-montane faunal elements of the Himalaya is coherent with isotope records as well as with fossil evidence of Late Paleogene and Miocene subtropical to temperate vegetation north of the Greater Himalaya (Su et al, 2019;Wang, Deng, & Biasatti, 2006;Xu et al, 2012), suggesting the existence of cloud forests in Paleo-Tibet.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Meanwhile, although proto‐Tibet reached 4.5 km in the mid‐Eocene, recent study based on a palm fossil from the Lunpola Basin has demonstrated the existence of a deep east‐west valley with elevation below 2.3 km in Tibet during the late Oligocene (Su, Farnsworth, et al, ). This valley and the surrounding high mountains formed a highly heterogeneous environment, including tropical and subtropical climates well suited to an Oligocene oak forest (Su, Farnsworth, et al, ). Several recent biogeographic studies of various subtropical disjunct lineages (e.g.…”
Section: Discussionmentioning
confidence: 99%